Foreword - Babalola Joseph Balogun; Emnet Tadesse Woldegiorgis (The Thinker)
The articles in this Special Issue were selected from responses to a call for abstracts on the theme “Generation of African Scholars and the Intellectual Legacies”. The idea was originally conceived by the late Professor Michael Cross, pioneer Director of the Ali Mazrui Centre for Higher Education Studies (AMCHES), University of Johannesburg, South Africa, to be a flagship project of the budding centre. It aimed to bring together, outstanding scholars from diverse disciplinary backgrounds and perspectives to critically investigate, analyse and document the intellectual legacies of African scholars, leaders, and institutions. Its central objective was to analyse the nature of African scholars’ contributions to knowledge production with the specific goal of influencing and/or shaping the higher education landscape, discourses, policies, and practices in Africa.